Ewolucja zasad podziału czystej nadwyżki w polskich spółdzielniach pracy - Grosfeld, Jan (Wydział Prawa i Administracji UAM, 1975)
This article deals with the problem of division of the co-operative surplus in Polish workers' productive co-operatives. At the beginning different types of members' benefits and their essence are characterized in comparison with those of private and state owned enterprises. In the second part the general rules of division of the co-operative surplus in Poland and the purposes of its allocation are presented i.e.: the development of the co-operative as a whole, the individual consumption of members and their collective consumption. The amounts from this surplus, defined as a percentage, replenish respective funds accumulated at the level of the co-operative or of the central union. They are also assigned for direct members' payments proportionally to wages. The theoretical rights of the co-operative self-overnment to determine the division of surplus are rarely realised in practice. The board of directors is acting as a driving belt transmitting decisions and recommendations from higher co-operative and state organs. The general assembly of members is accepting them formally only. This hasn't radically changed in the last period in spite of some attempts made in this field. Finally, the concrete proportions of division of surplus of the industrial cooperatives are analysed as well as their changes in years 1950 - 1955 and 957 -1971. This first period was particularly unfavourable for the co-operatives and for the co-operators as to the participation in the division of surplus and as to the liberty of action in choosing the purposes of division. In 1957 some important changes took place in this sphere however they were relatively stopped in the 60-ties. Since 1957 the proportions of division haven't much changed. In addition the current economic policy has often limited the part of surplus financing the purposes of consumption. The radical extension of the real rights of the co-operative and of its members in determining the division of surplus in general seems to be necessary.
Rules of Division of the Co-operative Surplus ant their Evolution in the Polish Industrial Co-operatives